Effects of Selection for High Litter-Weight on Reproductive Performance in Mice. - Baharin, K.; Beilharz, R. G. (1978)
The reproductive performances of two lines of mice selected for high litter-weight at nine weeks of age and a control line were compared based on data obtained after 15 generations of breeding. Twenty pairs of parents were bred per generation in the control line and ten pairs in each of the selected lines: at each generation the parents were mated only once. Calculation of inbreeding coefficients from pedigrees indicated a rapid rise in inbreeding coefficient in the selected lines. There was little response to selection for high litter-weight and in fact there was a general decline in reproductive performance associated with high levels of inbreeding in the selected lines although the relationship was not linear. Some initial response tn body weight gain was observed but even this trait showed a decline in later generations when inbreeding coefficient exceeded 40%.